Legal Review Of Narcotics Criminal Cases (Serang District Court Case Study Number 106/Pid.Sus/2025/PN SRG) - Tb Edya Rizky Maulana; M. Nassir Agustiawan; Mohammad Hifni (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
The issue of drug abuse is crucial given that narcotics have physical and mental effects. When used in appropriate doses and under the supervision of a doctor or psychiatrist, they can be used for medical or research purposes. This study aims to analyze the application of substantive criminal law and the public prosecutor's considerations in seeking punishment for Class I narcotics abuse, as outlined in District Court Decision No. 188/Pid.Sus/2022/PN Rkb. This study employed normative legal methods with a case study approach. This research was conducted in the city of Cilegon, specifically at the Cilegon District Attorney's Office, using primary legal materials, namely Law Number 35 of 2009 concerning Narcotics, and secondary legal materials, namely books, journals, and articles relevant to the research. After all data was collected, it was processed and analyzed qualitatively and then presented descriptively. This involves searching for and collecting data related to the object and problem under study, then systematically organizing it to obtain a clear and comprehensive picture. The research results indicate shortcomings by the Public Prosecutor in the application of sanctions and determination of the defendant's status, where the defendant was sentenced to seven years in prison and declared a Class I narcotics abuse offender. This research concludes that the sanctions and defendant's status were not commensurate with the weight of the evidence. The prosecution should have considered applicable legal provisions and mitigating factors. This indicates that the application of the law does not fully reflect the principle of justice. Therefore, greater precision and proportional consideration are required in the prosecution process of narcotics cases.